Family Factors, Caregiver Participation, and Outcomes in Pediatric Obesity Treatment - Irby, Megan Bennett (Wake Forest University, 2012)
Current data indicate that one of every three American children is overweight or obese, and more likely than not, those who are obese as children will be obese in adulthood. Though many pediatric obesity interventions have lead to statistically significant and clinically meaningful improvements in children's weight, a great number of children still show limited response to treatment, if at all. Expert recommendations for the treatment of pediatric overweight and obesity advocate for staged, multidisciplinary approaches that are family-based in nature. However, from the vast number of studies investigating family-based programs, most describe interventions with mother-child dyads, and there is rare mention of other caregivers and family members in the treatment process. Given the known familial link to weight status and the undeniable influence of family on children's behaviors, there is an intuitive need to focus on the role that family members play in the health behaviors of children, not exclusively mothers. The goal of this study was to examine patients and their families enrolled in a tertiary-care pediatric obesity treatment program (Brenner FIT) in an effort to identify associations between caregiver and family attendance and change in children's BMI z-scores. This study was a retrospective chart review utilizing patient data extracted from the Brenner FIT clinical database and medical records maintained electronically through Wake Forest Baptist Health.
Keywords: Caregivers; Family; Obesity; Pediatric; Treatment